HAK PASIEN DALAM PERSPEKTIF YURIDIS DAN KONVENSI BIOMEDIS - Gunawan Widjaja; Andina Rahmayani (Cross-border, 2020)
Health is a fundamental right for every human being. The right to live healthy is a human right for every citizen. In various international conventions, the protection of human rights is discussed, one of which is in the health sector. Indonesia generally regulates human rights in the health sector in laws and regulations as the legal basis for implementing health services. In health services, there are rights and obligations of the parties, namely health service providers (medical personnel, health workers) and health service recipients (patients) arising from therapeutic transactions. Each party must understand its rights and implement its obligations. In practice, the lack of communication between the parties involved in the implementation of health services, lack of understanding, or lack of information disclosure results in problems with patient rights. The purpose of making the theme of this paper is to find out the relationship between biomedical conventions and patient rights from a human rights perspective, as well as patient rights from a juridical perspective and their application in Indonesia. The results of this paper are the need for information disclosure, strengthening socialization related to rights and obligations as well as sanctions in case of violations in the application in the biomedical field and awareness of the parties concerned in understanding the rights and implementing their respective obligations in the implementation of health services.